Effect of intermittent high altitude hypoxia on gene expression in rat heart and lung - Deindl, E; Kolár, F; Neubauer, E; Vogel, S; Schaper, W; Ostádal, B (Physiological research, 2003)
Hypoxia has been identified as an important stimulus for gene expression during embryogenesis and in various pathological situations. Its influence under physiological conditions, however, has only been studied occasionally. We therefore investigated the effect of intermittent high altitude hypoxia on the mRNA expression of different cytokines and protooncogenes, but also of other genes described to be regulated by hypoxia, in the left ventricle (LV), the right ventricle (RV), atria and the lung of adult rats after simulation of hypoxia in a barochamber (5000 m, 4 hours to 10 days). Heme oxygenase-1 as well as transforming growth factor-beta1 showed an increased expression in all regions of the heart and the lung at different periods of hypoxia. For lactate dehydrogenase-A, we found a significant up-regulation in the RV and the lung, for lactate dehydrogenase-B up-regulation in the RV, but down-regulation in the LV and the atria. Vascular endothelial growth factor was up-regulated in the RV, the LV and the lung, but down-regulated in the atria. Its receptor Flk-1 mRNA was significantly increased in the atria and RV only. Expression of c-fos was found in the LV and RV only after 4 hours of hypoxia. The level of c-jun was significantly increased in the LV but decreased in the atria. Our data clearly demonstrate that intermittent hypoxia is a modulator of gene expression under physiological conditions. It differently regulates the expression of distinct genes not only in individual organs but even within one organ, i.e. in the heart.
Keywords: hemoxygenasa-1; regulace genové exprese enzymů; Adaptation, Physiological; cytokiny; tkáňová distribuce; Lung; krysa rodu Rattus; Hypoxia; zvířata; plíce; potkani Wistar; protoonkogenní proteiny; hypoxie; L-Lactate Dehydrogenase; Rats, Wistar; Male; Altitude; Heart; stanovení celkové genové exprese; Cytokines; hemová oxygenasa (decyklizující); Heme Oxygenase (Decyclizing); Heme Oxygenase-1; Proto-Oncogene Proteins; Heart Ventricles; fyziologická adaptace; Rats; Gene Expression Regulation, Enzymologic; myokard; Animals; Gene Expression Profiling; Myocardium; mužské pohlaví; L-laktátdehydrogenasa; srdeční komory; Tissue Distribution; srdce; nadmořská výška